2007
DOI: 10.1074/jbc.m705066200
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPβ Activates E2F-regulated Genes in Vivo via Recruitment of the Coactivator CREB-binding Protein/P300

Abstract: The E2F transcription factors play an essential role in regulating the G(1)- to S-phase transition of the cell cycle. Previous studies have identified the importance of interactions between E2Fs and other transcription factors as a mechanism for transcriptional control of a subset of E2F regulated target genes. However, the mechanisms responsible for E2F target gene specificity remain incompletely understood. Here we report that in a mammalian in vivo model of synchronized proliferation, C/EBPbeta occupancy on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Three separate studies with mRNA array analysis have shown that genes involved in liver regeneration change in groups following different dynamic patterns (17)(18)(19). Most up-regulated genes are involved in stress responses, nutrition and energy metabolism, cell cycle, and proliferation (18,20). We used a quantitative RT-PCR array to verify up-regulation of genes involved in cell cycle and proliferation and found that many cyclins and CDKs were up-regulated 2 days after 50% PH, which was in accordance with positive staining of PCNA and Ki67 in both SSLG and remaining livers, and upregulated cyclin G1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Three separate studies with mRNA array analysis have shown that genes involved in liver regeneration change in groups following different dynamic patterns (17)(18)(19). Most up-regulated genes are involved in stress responses, nutrition and energy metabolism, cell cycle, and proliferation (18,20). We used a quantitative RT-PCR array to verify up-regulation of genes involved in cell cycle and proliferation and found that many cyclins and CDKs were up-regulated 2 days after 50% PH, which was in accordance with positive staining of PCNA and Ki67 in both SSLG and remaining livers, and upregulated cyclin G1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cells without NPAT fail to enter S phase from quiescence (20). CBP/p300 is another protein phosphorylated by cyclin E/Cdk2 at G 1 /S transition to activate its histone acetyltransferase activity (21) and may function as a cofactor for many transcription factors including E2F (22). Interestingly, cyclin E/Cdk2 phosphorylates E2F-5 and increases its transcriptional activity through CBP/p300 recruitment (23).…”
mentioning
confidence: 99%
“…Previous studies have shown that C/EBP␤ may recruit other factors. C/EBP␤ binds to CREB binding protein/p300, and the complex regulates the expression of target genes, such as CD-RAP and E2F, by modifying chromatin structure via histone acetylation (40,41). It was also reported that C/EBP␤ can directly bind various regulators, such as NF-B, activating transcription factor, Fos, Jun, and Sp-1, by assisting other important transcription factors to bind DNA (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%